The Application of the Innovative Teaching for TOEFL IBT Preparation at English First Kayun Surabaya - Nukmatus Syahria; Hertiki Hertiki (JET ADI BUANA, 2016)
Since TOEFL is sat by students before being successfullyadmitted into various higher institutions of education at tertiary levelaround the world, they should reach and achieve a satisfactory pass inthe examination. It is an instrument to determine students’ ability tocarry out their programs of study in English. The TOEFL internetbased testing (iBT) measures the ability in using and understanding ofEnglish. It also assesses reading, listening, writing and speaking,focusing on integrating the four skills. The examination measuresstudents’ ability to use English language as a tool to communicateeffectively in academic settings. TOEFL iBT is also being taken bythose who want get automaticity for a promotion in their respectivejobs and application for visas. Therefore there is a necessity forlecturers to find out an innovative teaching model to use for theirconsumption. A model that should be effective and innovative in thelearning and teaching of English for foreign language learners thatcaters for local needs. This research is to find out the innovativeteaching and learning of English at English First (EF) which is situatedat Kayun, Surabaya. There are many other institutions that offerTOEFL iBT preparation. However, EF is chosen because of theteaching strategies are unique in a way that the practitioners are veryexperience and they themselves are native speakers of English. It ishoped that this study should be a fruitful effort in finding a goodmodel for teaching English to students who are motivated to learn andyet find it difficult to master the language in a non-Englishenvironment. This study also aims to give more description orinformation about the implementation of the innovative teaching ofTOEFL iBT examination for the lecturers in Adi Buana University intheir English language proficiency courses. The instruments used forthis study are interviews, classroom observations and field notes